Помогите пожалуйста!!!!!!


упростите выражение:

1)3*cos2x-3/tg2x+1-2

2)5tg2x*cosx+5sin2x*ctg2x

2

Ответы и объяснения

2012-05-12T00:26:01+04:00

1)3*cos2x-3/tg2x+1-2=((12*cos(x)^3-8*cos(x))*sin(x)-6*cos(x)^2+3)/(2*cos(x)*sin(x))

2)5tg2x*cosx+5sin2x*ctg2x=(10*cos(x)^2*sin(x)+20*cos(x)^4-20*cos(x)^2+5)/(2*cos(x)^2-1)

2012-05-12T02:01:39+04:00

1)3·cos2x-3/tg2x+1-2=

   ((12·cos(x)^3-8·cos(x))·sin(x)-6·cos(x)^2+3)/(2·cos(x)·sin(x))

 

2)5tg2x·cosx+5sin2x·ctg2x=

(10·cos(x)^2·sin(x)+20·cos(x)^4-20·cos(x)^2+5)/(2·cos(x)^2-1)